Harm Reduction Policies and Interventions for Injection Drug Users in Thailand - Tyndall, Mark (World Bank, Washington, DC, 2017)
The World Bank initiated a review of HIV prevention among injection drug users in Thailand, with the objective of providing technical assistance to strengthen national capacity to develop state-of-the-art injecting drug use harm reduction interventions. Thailand has received international recognition for its successful interventions to reduce the transmission of HIV among female sex workers and military recruits. It is looked upon as a role model for HIV education and awareness campaigns that include the extensive promotion and wide acceptance of condoms as an HIV prevention strategy. Thailand has the most progressive and comprehensive antiretroviral program in the region with a reported coverage of over 80 percent of eligible individuals. In 2001, it embarked on a progressive universal health care program that provides free access to a wide array of health care diagnostics and therapeutics for the people of Thailand. With these impressive achievements, it is remarkable how poorly Thailand has responded to the HIV epidemic among injection drug users (IDUs). From available data, it appears that the HIV prevalence rates among IDUs have remained high and stagnant over the last decade. Failure to provide effective interventions to reduce HIV transmission among drug users has resulted in unnecessary suffering, and for many, HIV-related death. Continued inaction threatens to undermine successful HIV prevention efforts in the country through ongoing HIV transmission among injection drug users and their sexual partners. The current focus on enforcement and punishment, along with the reliance on compulsory drug treatment centers, has done little to control drug use in Thailand. The unintended consequence of this approach has been to push drug users into precarious and dangerous environments that have directly led to risky drug using patterns and persistently high rates of HIV transmission. Adopting a harm reduction approach to deal with injection drug use could have a major impact on reducing HIV transmission as well as engaging drug users into better health care and effective drug treatment. This will require strong leadership in key government Ministries and related agencies so that the central stakeholders can roll out harm reduction programs. Thailand has the potential to greatly reduce the transmission of HIV among injection drug users and become a regional leader in harm reduction.